Delaying implant in high-risk calves has no benefit for health or feedlot performance - Munson, R.D.; Thomson, Daniel U.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Bovine respiratory disease is the most common and costly disease in the beef industry. Calves affected by bovine respiratory disease have a 53-lb decrease in finished weights and decreased quality grades compared with healthy cattle. Many stressors influence post-arrival health and nutrient intake, including weaning, marketing, transportation, co-mingling, genetics, previous nutrition, and health history. These stressors can negatively affect the immune system at a time when the animal is more likely to be exposed to infectious agents within the bovine respiratory disease complex. Feed intake by stressed calves is low, and low nutrient intake likely increases the negative effects of stress on the immune system. Delaying the initial steroid implant may reduce post-transit stress and improve carcass quality of feedlot cattle. This study was designed to examine the effects of administering initial steroid implants at feedlot arrival or 45 days after feedlot arrival on health, performance, and carcass characteristics of feeder calves at relatively high risk for bovine respiratory disease.
Keywords: Beef; Implant; Health performance; Feedlot performance; Bovine respiratory disease